Ethnozoologie De Balearica Pavonina (Grue Couronnée) Dans La Vallée Du Fleuve Niger: Cas Du Barrage De Kandadji - Soumaïla Hassane Hamani; Abdourahamane Illiassou; Youssoufa Issiaka; Ali Mahamane (European Scientific Journal, ESJ, 2021)
This study, undertaken in the zone of the Kandadji dam aimed to characterize the various biological and ecological aspects of the Balearica pavanina (crowned crane ) in the zone. Thedata collection was based on the information retrieval and the ethnozoologic investigations based on questionnaires administrated to 311 people from September, 15th to October 31st 2018. After an analysis of the data with the Excel software, someof the ethnozoologic elements were characterized. Hence, the crowned crane is a wader whose body plumage and neck are dark gray or black. It is mainly found in wetlands and grassland. This species is seen in the morning by 54,34% of the population and the evening by 33,11%. The sighting frequency of the crowned Crane varies from a day ago by 30,54% of the population to a week by 34,72%. It is found in every season of the year in colonies of approximately European Scientific Journal, ESJ ISSN: 1857-7881 (Print) e - ISSN 1857-7431 January 2021 edition Vol.17, No.3 www.eujournal.org 152 10 individuals. The study also showed that the drought is the principal natural threat with 87,13% of the surveys, followed by habitat destruction and hunting as anthropic threats with 38,26% and 36,01% of the survey, respectively. The crowned crane feeds on insects (33,11%) and seeds (51,76%). The eggs of B. pavonina are white (87,13) and of large size (81,99%). This species lays more than two eggs 65,91%) in the grasses (64,95%). The duration of blossoming of eggs is one month (83,92%) according to the survey. The crowned crane figures among endangered speciesand this study will contribute to the safeguarde this animal resource.La présente étude menée dans la zone du barrage de Kandadji a pour but principal de caractériser les différents aspects biologiques et écologiques de l’espèce Balearica pavonina dans la zone. La méthode de collecte des données s’est basée sur la recherche documentaire et aux enquêtes ethnozoologiques auprès de 311 personnes par des entretiens individuels, du 15 Septembre au 31 Octobre 2018. Les données collectées ont été analysées par le logiciel Excel. Quelques éléments ethnozoologiques ont été caractérisés. La Grue couronnée est un oiseau échassier dont le plumage du corps et du cou sont gris foncés ou noirs. Elle fréquente principalement les zones humides et herbeuses. Cette espèce est aperçue le matin par 54,34% de la population et le soir par 33,11%. La Grue couronnée est aperçue il y a un jour par 30,54% de la population et une semaine par 34,72%. Elle est rencontrée toutes les saisons de l’année à des colonies d’environ 10 individus. L’étude a European Scientific Journal, ESJ ISSN: 1857-7881 (Print) e - ISSN 1857-7431 January 2021 edition Vol.17, No.3 www.eujournal.org 151 montré que la sècheresse est la principale menace naturelle avec 87,13% des sondages. Ensuite, la destruction de l’habitat et la chasse constituent des menaces anthropiques respectivement avec 38,26% et 36,01% des sondages. Sa nourriture est constituée des insectes (33,11%) et graines (51,76%). Les œufs de B. pavonina sont blancs (87,13) et de grande de taille (81,99%). Cette espèce pond plus de deux œufs (65,91%) dans les herbes (64,95%). Le temps d’éclosion des œufs est de un mois (83,92%) selon les sondages. La Grue couronnée figure parmi les espèces en voie de disparition. Cette étude vise à contribuer à la préservation de cette ressource animale.